О некоторых биологических особенностях трихограммы желтой (Trichogramma cacoecia pallida Meyer), обитающей в горных садах Крыма - Дядечко, Н.П.; Цыбульская, Г.Н.; Францевич, Л.А. (Вестник зоологии, 1975)
The population dynamics, periods of development, fecundity and the sex ratio of the progeny were studied in Tr. cacoecia pallida and Tr. evanescens under field conditions in the Crimea (Alushta district). The natural infestation of eggs of the codling moth by the above-mentioned parasites amounted to 45%. The applications of dipterex (2 kg/ha). hardly affecting the host population, caused 2-3 times decrease of the parasite infesta- tion. Nine generations of Trichogramma were observed for the period under study. The development rate was directly proportional to temperature and identical in both species. The sex ratio (:) was 3.9:1 in Tr. evanescens and 4.6:1 in Tr. cacoecia pallida. Fecundity of Tr. cacoecia pallida was 35-40 eggs on the eggs of Sitotroga cereallella, fecundity of Tr. evanescens being 6.8 eggs less under the same conditions.